Incidencia de un programa en la ansiedad precompetitiva en deportistas de un club de patinaje de la ciudad de Ibagué. (2022)
The present investigation determines if the application of a program to reduce anxiety based on mindfulness techniques has an impact on sports performance, for this a study was carried out in a group of skating athletes between 9 and 15 years of age of a club of the city of Ibagué applying the Revised Competitive Anxiety Inventory-2 (CSAI-2R) in the form of pretest and posttest. The research is of a quasi-experimental type with a quantitative approach, of an empirical-analytical paradigm, the main variables to be related for the analysis were the Age and Gender of the participants. In the pretest stage, levels of Somatic and Cognitive anxiety were evidenced with Medium or High values and a Low level for the Self-confidence category. It was possible to demonstrate in the postets stage and after having applied the pilot of the program, that the levels of Somatic and Cognitive anxiety passed to Low levels and the category of Selfconfidence increased to a Medium or High level, achieving satisfactory results with respect to the application of the pilot program.